A Hypocephalus with Odd Iconography and Poor Writing in the Berlin Museum - Miatello, Luca (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
This paper proposes the publication of the hypocephalus Berlin ÄM 17336, characterized by bizarre iconographic details and poor hieroglyphic writing. Vignettes and texts in specimens of similar typology are examined and compared. The texts around the edge and in the various registers differ from those in the extant corpus of hypocephali, but in general they can be attributed to known typologies of text. Although the odd iconography and the poor handwriting suggest that the specimen is a modern forgery, other elements indicate that it could have been made in the Roman period by an unskilled person enticed by satirical material.